THE BOOK OF ITALIAN COOKING - Budgen, June, contributor 637695; Bush, Sarah, contributor 637696; Harries, Kerenza, contributor 231093; Hurst, Jacqui, contributor 637697; Mackley,Lesley, contributor 367781; Murfitt, Janice, contributor 173943; Norman, Cecilia, contributor 637698; Norwak, Mary, contributor 312969; Passmore, Jackie, contributor 231233; Rhodes, Lorna, contributor 637699; Rutherford, Lyn, contributor 637700; Steele, Louise, contributor 207529; et al. (Surrey, UK. : TEDSMART : Salamander Books Ltd., 1991)
Nasrul Humaimi Mahmood